PENGARUH KERAGAMAN PRODUK DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN DI SAHABAT MOTOR PALEMBANG - Muhammad Bagus Saputra; Muhammad Said; Putri, Yuni Adinda (Jurnal Bisnis Terapan, 2024)
The purpose of this study is to investigate the effect of product innovation and word of mouth on the sales of Sahabat Motors Palembang. This study used primary and secondary data obtained from interviews. Combining 25 SPSS models and data from 100 respondents, product category significantly influenced 3,085 purchase decisions. Further analysis shows that the t values in the t table are 3085, 1983 and higher, which indicates a higher t score. T table or 6.725 1. 983 is greater than it. Because it affects your purchasing decision. 6.725 Since y = 14.713 + 0.188X1 + 0.726X2 is small. Productivity Effects 58 Forces and Static Connections greatly influences the purchase choice. The result of this was in line with those studies which have been conducted before related to the techniques of word of mouth in promotion and other techniques which are usually used in the marketing and promotions to accelerate the purchasing decisions of the potential buyers.